2000
DOI: 10.1103/physrevlett.85.582
|View full text |Cite
|
Sign up to set email alerts
|

Noncapillary-Wave Structure at the Water-Alkane Interface

Abstract: Synchrotron x-ray reflectivity is used to study the interface between bulk water and bulk n-alkanes with carbon numbers 6 through 10, 12, 16, and 22. For all interfaces, except the water-hexane interface, the interfacial width disagrees with the prediction from capillary-wave theory. The variation of interfacial width with carbon number can be described by combining the capillary-wave prediction for the width with a contribution from intrinsic structure. This intrinsic structure is determined by the gyration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
188
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(220 citation statements)
references
References 23 publications
28
188
2
2
Order By: Relevance
“…1B. The fitted values of roughness (4.2 → 4.9 Å) for all fits of the PB/MD model are within 2 SDs (i.e., within ± 0:4 Å) of the values calculated from capillary wave theory using our interfacial tension measurements (10,21) (Table S1). …”
Section: Resultsmentioning
confidence: 69%
“…1B. The fitted values of roughness (4.2 → 4.9 Å) for all fits of the PB/MD model are within 2 SDs (i.e., within ± 0:4 Å) of the values calculated from capillary wave theory using our interfacial tension measurements (10,21) (Table S1). …”
Section: Resultsmentioning
confidence: 69%
“…The possibility of such a phase transition at an alkanewater interface has been discussed for a long time [3,4,5,6,7]. The observation of a solid -liquid phase transition at the n-hexane -water interface in the Gibbs monolayer of a surfactant is reported in this work.…”
mentioning
confidence: 63%
“…However, several theoretical and experimental studies have demonstrated the existence of a smooth intrinsic density profile with a finite width [25][26][27][28][29][30]44 .…”
Section: Interfacial Tensionmentioning
confidence: 99%